Delivery of Anti-miRNA-221 for Colorectal Carcinoma Therapy Using Modified Cord Blood Mesenchymal Stem Cells-Derived Exosomes - Han, Siqi; Li, Guangchao; Jia, Meng; Zhao, Yulu; He, Chenglong; Huang, Mengxi; Jiang, Longwei; Wu, Meijuan; Yang, Jiahe; Ji, Xiaoqin; Liu, Xiaobei; Chen, Cheng; et al. (Frontiers in Molecular Biosciences, 2021)
Background: Exosomes, as natural intercellular information carriers, have great potential in the field of drug delivery. Many studies have focused on modifying exosome surface proteins to allow drugs to specifically target cancer cells. Methods: In this study, human cord blood mesenchymal stromal cell-derived exosomes were used in the delivery of anti-miRNA oligonucleotides so as to be specifically ingested by tumor cells to perform anti-tumor functions. Mesenchymal stem cells modified by the fusion gene iRGD-Lamp2b were constructed to separate and purify exosomes, and the anti-miRNA-221 oligonucleotide (AMO) was loaded into the exosomes by electroporation. Results: The AMO-loaded exosomes (AMO-Exos) effectively inhibited the proliferation and clonal formation of colon cancer cells in vitro, and it was further found that AMO-Exos was taken up by tumor cells through interaction with the NRP-1 protein. The results of a xenograft tumor model also showed that iRGD-modified exosomes were obviously enriched in tumor sites, exerting excellent anti-tumor efficacy. In vivo imaging showed that exosomes were mainly distributed in liver, spleen, and lung tissues. Conclusion: Our results suggest that genetically modified exosomes could be an ideal natural nanostructure for anti-miRNA oligonucleotide delivery.